Behandlung von erwachsenen Patienten mit ambulant erworbener Pneumonie – Update 2021 - Ewig, S.; Kolditz, M.; Pletz, Mathias Wilhelm; Altiner, A.; Albrich, W.; Droemann, D.; Flick, H.; Gatermann, S.; Krueger, S.; Nehls, W.; Panning, M.; Rademacher, J.; et al. (Pneumologie, 2021)
The present guideline provides a new and updated concept of the management of adult patients with community-acquired pneumonia. It replaces the previous guideline dating from 2016.The guideline was worked out and agreed on following the standards of methodology of a S3-guideline. This includes a systematic literature search and grading, a structured discussion of recommendations supported by the literature as well as the declaration and assessment of potential conflicts of interests.The guideline has a focus on specific clinical circumstances, an update on severity assessment, and includes recommendations for an individualized selection of antimicrobial treatment.The recommendations aim at the same time at a structured assessment of risk for adverse outcome as well as an early determination of treatment goals in order to reduce mortality in patients with curative treatment goal and to provide palliation for patients with treatment restrictions.
CRIS-Team Scopus Importer:2022-09-26